2008
DOI: 10.1016/j.compscitech.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of alumina–zirconia–Nb micro–nano-hybrid composites

Abstract: The multi-scale and multi-phase hybrid composite ceramic-metal materials Al 2 O 3 -nZrO 2 -Nb are successfully fabricated. Their mechanical properties are better compared to the single-phase alumina materials and conventional alumina-Nb composite materials. The coexist function of nano-scale ZrO 2 , which can increase the initial toughness and strength, and the micrometer lamellar Nb particles which increase the toughness, flaw tolerance and crack growth resistance, improve notably the mechanical properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…And several investigations showed that a smaller grain size (grain refinement) in alumina ceramics led to improved mechanical properties [5,[18][19][20][21][22]. The mechanical strength of Al 2 TiO 5 ceramics also increased as the grain size decreased [23].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…And several investigations showed that a smaller grain size (grain refinement) in alumina ceramics led to improved mechanical properties [5,[18][19][20][21][22]. The mechanical strength of Al 2 TiO 5 ceramics also increased as the grain size decreased [23].…”
Section: Introductionmentioning
confidence: 93%
“…However, the relatively high sintering temperature and low fracture toughness have limited its applications to some extent. It has been proved that incorporating suitable second phases into alumina is an effective way to lower its sintering temperature, control its microstructure and therefore improve its mechanical properties [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…14), that open the possibility to tailor new materials with toughening mechanisms operating at different scales. 80 For a scale below the one of the matrix microstructure, this enhances the "intrinsic" fracture properties of the material. This intrinsic increase of resistance to crack initiation and propagation should lead to an increase in the catastrophic failure strength.…”
Section: Case Study 2: Al 2 O 3 -Nzro 2 /Nbmentioning
confidence: 98%
“…A major toughening mechanism in metal particulate reinforced ceramics is crack surface bridging by the plastically stretched ductile particulates [3][4][5]. Extensive efforts have been made to understand toughening and the crack growth resistance behavior of the composites since 1980s [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%